Peningkatan Kemampuan Menulis Cerpen Melalui Metode Egp (Emosional Gerak Cepat Dan Perevisian) Berbasis Media Audio Visual Siswa Kelas IX SMPN 3 Pallangga - Rahmadana Rahmadana; Marwiah Marwiah; Maria Ulviani (PT. ALHAFI BERKAH INDONESIA, 2023)
The main problem in this research is how to apply the EGP method based on audio-visual media to improve the ability to write short stories in class IX students of SMPN 3 Pallangga, Gowa Regency. This study aims to improve the ability to write short stories through the EGP method based on audio-visual media in class IX students of SMPN 3 Pallangga. This type of research is class action research (Class Action Research). Research procedures include planning, implementation of action, observation and reflection. The subjects in this study were 25 students of class IX 6 at SMPN 3 Pallangga, Pallangga Regency. The results showed that in the first cycle, out of 25 students, only 5 students met the minimum completeness criteria (KKM) or were in the low category. Classically it has not been fulfilled because the average value obtained is 69.56%. Whereas in cycle II where out of 25 students there were 23 students who had fulfilled the KKM and classically it had been fulfilled, namely the average value obtained was 84.36% or was in the very high category. Based on the results of the research above, it can be concluded that the ability to write short stories in class IX students of SMPN 3 Pallangga, Gowa Regency through the application of the EGP method based on audio-visual media has increased.